Effects of prenatal stress and postnatal high fat diet feeding on BALB/c mice metabolism - Quiroga, Sofia (2019)
Fil: Quiroga, Sofia. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Científicas; Argentina